MULTI-ANALYTIC FACTORS PREDICTING ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AMONG PERSONNEL OF NIGERIA SECURITY AND CIVIL DEFENCE CORPS IN THE SOUTHWEST, NIGERIA (2016)
Organisational citizenship behaviour (OCB) implies acting beyond the formal job description for the purpose of corporate and individual benefits. This is waning in the Nigeria Security and Civil Defence Corps (NSCDC). This scenario has been rendering the commitment of the NSCDC towards the combat of vandalism, protection of critical national assets, supervision of private guards and management of disasters to be less effective. Past studies on OCB among para-military personnel were only on the organizational factors and with no consideration of the NSCDC. This study, therefore, investigated the predictive strength of multi-analytic factors (creativity, leadership behaviour, social innovation, social intelligence, religiosity, age, job tenure, marital status, gender, educational level, organizational tenure and job cadre) on OCB among personnel of the NSCDC in the Southwest, Nigeria. The Social Exchange Theory provided the study framework, while descriptive survey design of the ex-post facto type was adopted. Using multistage sampling technique, a random sample of 1,696 personnel (966 males) were selected from 24 divisional offices (DOs) of the NSCDC. The DOs were randomly selected from the three area commands and three state commands respectively in Ogun (5), Osun (10) and Oyo (9) made up of officers and men. Organisation Citizenship Behaviour (r=0.83), Multifactor Leadership (r=0.87), Religiosity (r=0.93), Tromso Social Intelligence (r=0.90), Creativity (r=0.86) and Social Innovation (r=0.91) scales were used for data collection. Data were analysed using Pearson product moment correlation and Multiple regression at 0.05 level of significance. The personnel average age was 31.6. Other socio-demographic factors (in %) were: job tenure: the number of years spent on the job ranged from 8.32-10.7 years, gender: male (58.3), female (41.7), educational level: SSCE/WAEC (13.4), Trade Test (7.7), OND (11.3), NCE (14.0), HND (27.2), University Degree (18.7), Master (6.7), Ph.D. (1.0), job cadre: Corps Assistance (26.5), Inspectorate (55.4), Superintendent (18.1), marital status: Single (27.3), Married (68.0), Divorced (2.0), Separated (1.7), Widowed (1.0) and organisational tenure: 1-5years (38.1), 6-10years (23.8), 11-15years (38.1).The OCB of NSCDC personnel correlated positively with leadership behaviour (r=.648), social intelligence (r=.339), social innovation (r=.548) and job cadre (r=.062). There was a significant joint prediction of the independent variables on OCB (F(12, 1562)= 230.03; R2=0.639) and this accounted for 63.9% of its variance. However, job cadre (β=-.038), organisational tenure (β= -.189), leadership behaviour (β=-.001) and religiosity (β=-.008) were found to be negative predictors of OCB. Social innovation (β=.691); age (β=.389); gender (β=.274); educational level (β=.212); marital status (β=.005); creativity (β=.005); job tenure (β=.072) and social intelligence (β=.037) contributed positively to the prediction. Creativity, social intelligence, social innovation, age, job tenure, gender and educational level positively influenced organisational citizenship behaviour among the personnel of Nigeria Security and Civil Defence Corps while older, experienced, female, highly educated, junior and transferred service personnel were found to engage more in organisational citizenship behaviour. Hence, counselling and organisational psychologists should take into cognisance these multi-analytic factors found to be significant in the effective management of the personnel of Nigeria Security and Civil Defence Corps as whole. Key words: Organisational citizenship behaviour, Multi-analytic factors, Nigeria security and civil defence corps, Southwest Nigeria Word count: 484